TOXIC LEADERSHIP: CONSEQUENCES FOR EMPLOYEE WELLBEING AND TURNOVER INTENTIONS - Yulniarmah; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (RADJA PUBLIKA, 2025)
Toxic leadership, characterized by destructive behaviors such as bullying, narcissism, and unpredictability, poses a severe threat to organizational health. This article examines its profound consequences, arguing that such leadership directly and indirectly erodes employee wellbeing and fuels turnover intentions. The analysis demonstrates that toxic leaders actively push employees out by creating a hostile environment, while simultaneously dissolving the pull of loyalty and commitment. This dual assault manifests in significant psychological distress, physical health issues, and social strain for employees. Crucially, the pathway to turnover often involves presenteeism—a costly period of disengagement. The article concludes that proactive organizational intervention, including leader accountability and robust employee support systems, is not merely beneficial but essential to mitigate these damaging effects and safeguard both human capital and operational integrity.